APPROACHES TO RESEARCHING BORDER REGIONS: WRITING THE HISTORY OF LATGALIA - Gibsone, Katerine (Via Latgalica, 2014)
While there has been increasing interest in the history of border regions in recent years, this has not been accompanied by a growing discussion of theoretical or methodological considerations. Using the case study of Latgalia, this paper aims to shed light on some of the conceptual and practical methodological considerations and challenges inherent in writing the history of border regions. The author argues that the study of the history of border regions necessitates a decentring of national history and a move to transnational (or non/a-nationally construed) history.